Implementation of Celebrating Diversity in the Global Diversity Theme Pancasila Student Profile Strengthening Project (P5) in Class VB SD Baiturrohman GMI - Rizkiyah, Maulida Putri; Jamalah, Lailah (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
Character education is now a focal point in Indonesia's education system, aligning with national development goals to cultivate students who embody faith, piety, noble character, health, knowledge, competence, creativity, independence, and responsibility. To counter the erosion of moral values in adolescents influenced by modernization and globalization, effective character education implementation is crucial. Since the 2013 curriculum is deemed ineffective, the project-based independent curriculum aims to fortify students' characters. SD Baiturrohman GMI Jember is among the schools that have adopted this approach. This qualitative research illustrates the implementation of the Pancasila Student Profile Strengthening Project (P5), emphasizing tolerance in Class V-B SD Baiturrohman GMI. P5, themed